2017
DOI: 10.3390/nano7120432
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Corrosion Resistance Properties of Electroplated Chitosan-Zn1−xCuxO Composite Thin Films

Abstract: Novel chitosan–zinc copper oxide (Zn1−xCuxO) composites were electrochemically synthesized through galvanostatic deposition. The prepared chitosan-based composite thin films were elaborately investigated to determine their structural, morphological, compositional, impedance, and corrosion properties. X-ray diffraction analysis was performed to reveal their structural orientation of composite thin films. Energy dispersive analysis by X-ray evidently confirmed the existence of Zn, Cu, and O in the composite thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…Figure 3a displays the UV–vis spectra for nanocomposites S1–S5. The observed broad absorption peak at 265 nm for S1 is related to the n → σ ∗ transport of the CS amino group [40,46]. The absorption peak intensity decreases linearly with increasing metal matrix ratio of the Mn and Zn sources used to synthesize nanocomposites S2–S5, which is strongly correlated with our earlier observations [4].…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Figure 3a displays the UV–vis spectra for nanocomposites S1–S5. The observed broad absorption peak at 265 nm for S1 is related to the n → σ ∗ transport of the CS amino group [40,46]. The absorption peak intensity decreases linearly with increasing metal matrix ratio of the Mn and Zn sources used to synthesize nanocomposites S2–S5, which is strongly correlated with our earlier observations [4].…”
Section: Resultssupporting
confidence: 80%
“…The CS was synthesized from chitin through the deacetylation method [4,40]. Initially, crab shells were collected, cleansed in seawater, and then dehydrated in sunshine for 1 day.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, its matrix could be modified either in the bulk or interface. The possibility of using inhibitor-loaded chitosan systems to protect metallic substrates, either as components in multi-layer coatings systems, or as free-standing films was revealed [25][26][27][28][29][30][31]. It was also found that CaP/chitosan coating effectively protected the AZ91D magnesium alloy from corroding.…”
Section: Introductionmentioning
confidence: 99%
“…It is the cationic property that gives Chitosan (CHT) the ability to penetrate mucous layers in biomedical applications, perform an antimicrobial function in food preservatives, and trap dyes and metals in waste water [19]. It is also being used in technical applications such as packaging and decontamination, because of its physico-chemical properties, such as hydrophobicity, thermal stability, and mechanical performances [20]. These properties, unique to CHT, combined with high porosity and surface area by its nanosize, render it important for a range of different functional systems.…”
Section: Introductionmentioning
confidence: 99%